TINGKAT STRESS KERJA GURU DI SEKOLAH INKLUSI - Uluwiyya, Rahma; Sriati, Aat; Kosim, Kosim (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
Teachers in inclusive education have different responsibilities from teachers in general schools because they have to interact directly with both children with special needs and children without special needs who certainly have different characteristics. Teachers need special knowledge and skills to handle, teach, and guide children with special needs. This is certainly a big responsibility that must be carried out by teachers in inclusive schools. The amount of responsibility can cause increased job stress in teachers. The purpose of this study was to determine the level of job stress among teachers in inclusive schools. The research was conducted in June 2024 in one of the inclusive schools in Cimahi City with a research population of 73 teachers. Sample determination using a total sampling technique. This study the Teacher Stress Inventory (TSI) to measure the level of teacher job stress. The results of this study are that most teachers in inclusive schools experience job stress with the following category distribution. There were 38.4% of teachers experiencing moderate stress, 28.8% experiencing high stress, and 1.4% of respondents experiencing very high stress. However, some respondents only experienced mild stress (23.3%) and very mild stress (8.2%). Based on this study, it can be concluded that teachers who teach in inclusive schools mostly experience high stress. It’s suggested that institutions can create a positive environment for teachers and provide counseling services for educators who experience very mild, mild, moderate, high, or even very high job stress.